Tribal women in India - Rao, V. M. 1954- (Jaipur : ABD Publishers, 2006)
Study on Girijan Cooperative Corporation and association of tribal women in its activities in Andhra Pradesh.
Includes statistical tables.
Includes bibliographical references (p. [197]-199) and index.
Keywords: Girijan Cooperative Corporation; Cooperative societies -- India -- Andhra Pradesh; Cooperative societies -- India -- Andhra Pradesh -- Statistics